Therapeutic Effect of Lebanese Cannabis Oil Extract in the Management of Sodium Orthovanadate-Induced Nephrotoxicity in Rats - Habchy, Chistabel (2023)
The current study investigated the therapeutic effect of Lebanese Cannabis oil extract against Sodium orthovanadate-induced nephrotoxicity. Sodium orthovanadate is a non-selective inhibitor of protein tyrosine phosphatases that are known to play major modulator roles in cell signaling and survival. Kidney is a major target for the toxicity of Sodium orthovanadate causing several types of renal injury, including glomerulosclerosis, inflammation and tubular damage. The effect of Cannabis oil on Sodium orthovanadate-induced nephrotoxicity was studied in vivo using Sprague Dawley male rat model. Rats were intraperitoneally injected with 10mg/Kg Sodium orthovanadate for 10 days followed by 5mg/Kg, 10mg/Kg, or 20mg/Kg intraperitoneal injection of Cannabis oil extract starting day 4 till day 10. Body weight of rats were monitored during the study and clinical parameters including serum urea, creatinine, and electrolytes were measured as well as kidney and heart pathology. Rats that were injected with Sodium orthovanadate displayed a marked reduction in body weight, increase in serum creatinine and urea in comparison to the control group. All doses of Cannabis oil caused significant decrease in serum urea, as well as in serum creatinine at a dose of 20mg/Kg. In addition, a marked reduction in renal vascular dilatation, scattered foci of acute tubular necrosis, and numerous mitosis in tubular cells was observed in Cannabis oil treated rats (20mg/Kg) as compared to the Sodium orthovanadate- treated group. In conclusion, the primary findings demonstrate a potential therapeutic effect of Cannabis oil on kidney damage induced by Sodium orthovanadate.